2023
DOI: 10.1039/d2cy01629j
|View full text |Cite
|
Sign up to set email alerts
|

Benign catalytic oxidation of potato starch using a homogeneous binuclear manganese catalyst and hydrogen peroxide

Abstract: Oxidation is an excellent way to improve the properties of native starches. After oxidation, products are easier to handle due to a lowered paste viscosity in water, an improved stability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…These results confirm that the catalyst stability is an important limiting factor in our reaction. This was in accordance with our previous work on the oxidation of starch, which showed that control of H 2 O 2 addition was crucial . We found batch addition of H 2 O 2 degraded the catalyst faster, and indeed, batch addition of H 2 O 2 caused a drop in HMF conversion as well, from 57% to 22% (cf.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm that the catalyst stability is an important limiting factor in our reaction. This was in accordance with our previous work on the oxidation of starch, which showed that control of H 2 O 2 addition was crucial . We found batch addition of H 2 O 2 degraded the catalyst faster, and indeed, batch addition of H 2 O 2 caused a drop in HMF conversion as well, from 57% to 22% (cf.…”
Section: Resultssupporting
confidence: 92%
“…Mncat and H 2 O 2 in H 2 O. This general procedure was adapted from Saisaha et al 22 and Broekman et al 28 For specific conditions, see the main text and the Supporting Information (Tables S1 and S2).…”
Section: Oxidation Of Hmf Bymentioning
confidence: 99%
“…Compared with acid-hydrolyzed starch, oxidized starch has a lower viscosity ratio between cold and hot paste compared with raw starch, making it less prone to retrogradation and widely used as a sizing agent to improve the mechanical and film-forming properties of textiles (Vanier et al 2017). Researchers used hydrogen peroxide (Broekman et al 2023;Hou et al 2007;Sangseethong et al 2010), sodium hypochlorite (Carlos Bustillos-Rodriguez et al 2019;Xu et al 2022;, potassium permanganate (Ma et al 2022), sodium periodate (Ozkan & Ozgunay 2021;Xi et al 2022), chlorine dioxide (Guo et al 2014), ozone gas (Chan et al 2011;Chan et al 2009), persulfate, and other oxidants to promote the oxidation of starches from different sources. However, oxidized starch is affected by the presence of α-1,4-glycosidic bonds are sensitive to heat, shear, and oxidation, resulting in poor viscosity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with acid-hydrolyzed starch (HS), oxidized starch has a lower viscosity ratio between cold and hot paste compared with raw starch, making it less prone to retrogradation and widely used as a sizing agent to improve the mechanical and film-forming properties of textiles. 5 Researchers have used hydrogen peroxide, [6][7][8] sodium hypochlorite, [9][10][11] potassium permanganate, 12 sodium periodate, 13,14 chlorine dioxide, 15 ozone gas, 16,17 persulfate and other oxidants to promote the oxidation of starches from different sources. However, oxidized starch is affected by the presence of a-1,4-glycosidic bonds and is sensitive to heat, shear and oxidation, resulting in poor viscosity and viscosity stability.…”
mentioning
confidence: 99%